The Effects of Creative Problem Solving Learning Model on Students' Mathematical Problem Solving Ability: Meta Analysis - Asyifa Rahmawati; Dadang Juandi; Kartika Yulianti (STAI Hubbulwathan Duri, 2023)
The Creative Problem Solving (CPS) learning model is often used as an alternative learning model that is considered to be able to improve students' mathematical problem-solving abilities. Therefore, many studies have related to the effect of the Creative Problem Solving (CPS) learning model on the mathematical problem-solving ability of students in Indonesia. The purpose of this study is to synthesize primary studies in the form of national journal articles or national proceedings with inclusion criteria: published in 2013-2022; articles published in national journals or national proceedings or indexed by SINTA; articles with experimental or quasi-experimental methods involving the experimental group and the control class; articles that include statistical data (sample size, mean value, standard deviation). The results of the study found that the overall effect size was 0.655 in the high effect category. Analysis of the level of variation in the study was carried out by considering two moderating variables, namely education level and sample size. The difference in education level was obtained ( and ), and the difference in sample size was obtained ( and ), which did not change the effect size of the implementation of the Creative Problem Solving (CPS) learning model on students' mathematical problem-solving abilities.